Women's Sexuality: From Aging to Social Representations. (24th July 2013) - Ringa, Virginie; Diter, Kevin; Laborde, Caroline; Bajos, Nathalie
Abstract Introduction Studies designed in northern countries show that most women are still sexually active after the age of 50. Many factors other than hormones influence sexual life in and after middle age; they include social status, personal characteristics, physical and psychological conditions, relationship factors, and social representations of sexuality. Aim This study aims to analyze various components of sexuality, including its social representations, among women aged 45–55 years, as they reach menopause. Methods Comparison of three groups: all postmenopausal women (277), postmenopausal women not currently using hormonal treatment (HT) (209), postmenopausal women currently using HT (68), with a reference group of premenopausal women (408). All were recruited in a national general population‐based survey of sexual behaviors and interviewed by telephone. Main Outcome Measures Practices, sexual function, satisfaction, and representations and expectations concerning sexuality. Results The women did not differ according to menopausal status for sexual activity, practices (wide range of practices beyond sexual intercourse), dysfunction, or satisfaction. They also attributed equal importance to sexuality. Nevertheless, although postmenopausal women not using HT did not report less sexual activity than premenopausal women, they were less likely to consider that a 3‐month period without sex is a sign of difficulty in a relationship (30.3% vs. 47.7%; odds ratio: 0.35 [0.21–0.57], P = 0.000). This difference was not observed between postmenopausal women using HT and premenopausal women. Conclusions Our results suggest that for middle‐aged women who are at the onset of menopause, the biological/hormonal changes characterizing menopause do not negatively affect sexual life. Any negative reported effects on sexuality are more likely due to anticipation or negative representations of sexuality around menopause than to biological or hormonal effects. The effect of menopause at this point in women's lives may thus be more symbolic than biological, expressed as a form of anticipation of old age. Ringa V, Diter K, Laborde C, and Bajos N. Women's sexuality: From aging to social representations. J Sex Med 2013;10:2399–2408.